Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1001/jama.1997.03550080047038
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Home Visitation on Maternal Life Course and Child Abuse and Neglect

Abstract: This program of prenatal and early childhood home visitation by nurses can reduce the number of subsequent pregnancies, the use of welfare, child abuse and neglect, and criminal behavior on the part of low-income, unmarried mothers for up to 15 years after the birth of the first child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
293
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 981 publications
(303 citation statements)
references
References 15 publications
6
293
0
4
Order By: Relevance
“…That abusive parents often recall abusive incidents as beginning with instrumental corporal punishment (Coontz & Martin, 1988;Gil, 1973;Kadushin & Martin, 1981) confirms this connection. Indeed, many abuse prevention efforts explicitly target the reduction of parents' reliance on corporal punishment as a goal (e.g., Azar, 1989;Olds et al, 1997;Thompson, Ruma, Brewster, Besetsney, & Burke, 1997;Wolfe, Sandler, & Kaufman, 1981).…”
Section: Direct Experience: Physical Abusementioning
confidence: 99%
“…That abusive parents often recall abusive incidents as beginning with instrumental corporal punishment (Coontz & Martin, 1988;Gil, 1973;Kadushin & Martin, 1981) confirms this connection. Indeed, many abuse prevention efforts explicitly target the reduction of parents' reliance on corporal punishment as a goal (e.g., Azar, 1989;Olds et al, 1997;Thompson, Ruma, Brewster, Besetsney, & Burke, 1997;Wolfe, Sandler, & Kaufman, 1981).…”
Section: Direct Experience: Physical Abusementioning
confidence: 99%
“…PPI/psychoeducational home visitation (PHV) was based on the home visiting programme developed by Olds et al, [216][217][218] augmented by 'a variety of cognitive and behavioural techniques in order to address parenting skill deficits and social-ecological factors, such as limited personal resources, poor social support, and stresses in the home associated with maltreatment' (p. 794). The interventions were provided by trained, master's level therapists, on a weekly basis over the course of 1 year.…”
Section: Attachment-orientated Interventionsmentioning
confidence: 99%
“…Research from the USA (Olds et al, 1997) has demonstrated the benefits of preventive home visiting. In this 15-year follow-up of a randomised controlled trial of home visiting for poor mothers during pregnancy and up to the child's second birthday, there were significant psychosocial benefits for mothers and significantly less abuse and neglect of children.…”
Section: Interventions By the Primary Care Teammentioning
confidence: 99%